Intracyclic speed and coordination vs. fatigue in swimming - Tella, V.; Llop, F.; Jorda, J.; Madera, J.; Benavent, J. (Biomechanics and Medicine in Swimming X, 2006)
Intracycle speed variations have been widely studied. However, few studies have focused on the fatigue effect on such intracycle speed in freestylers. The aim of this study was to analyse such effects. Hence, a synchronized speedmeter connected with a video camera was used and 17 swimmers were recorded with and without fatigue conditions. A complete cycle, four phases average speed and arms coordination were analysed in both conditions. There is a correlation of the average speed with phases l and 3-speed in both genders with and without fatigue. Also phase 2 speed in male and phase 4 in female swimmers are related to the average speed with fatigue. Coordination is related to the phase 4 in female swimmers with fatigue. Summarizing, the whole analysis of the partial speed and the coordination index gives us relevant information about intracycle kinematic responses of freestyle swimmers.